Synthesis, Characterization and Radical Scavenging Activities of 1,3-Disubstituted Benzimidazolium Salts - Düşünceli, Serpil Demir; Karatepe, Buket; Keser, Serhat (Niyazi BULUT, 2025)
The reaction of N-substituted benzimidazole and alkyl halides (benzyl bromoacetate and trifluoromethoxybenzyl bromide) gave a series of 1,3-disubstituted benzimidazolium salts. The structure of synthesized compounds was confirmed by various spectroscopic techniques such as 1H, 13C and 19F NMR spectroscopy, FT-IR and elemental analysis. Biological efficiency of these compounds was evaluated by antioxidant activities like ABTS, OH and DPPH radical scavenging activity.
Keywords: Biochemistry and Cell Biology (Other); Biyokimya ve Hücre Biyolojisi (Diğer)